Позитивне значення тривалого використання берлітіону у лікуванні хворих із діабетичною ретинопатією - Сухіна, Л. О.; Голубов, К. Е. (Clinical Endocrinology and Endocrine Surgery, 2010)
Investigation of the influence of medication Berlthion on the development of diabetic retinopathy in 95 patients whit diabetes mellitus. The duration of course of treatment was equal to 4 years. It has been noted a reliable improvement in the pattern of the fundus of the eye, of indices of conjunctive microcirculation, of visual functions.